The impact of enterprise resilience and HRM practices on performance: Findings from fsQCA - Liu, Bo; Li, Yan; Tang, LinHua; Zhao, Yipeng; Chang, Haodong (Frontiers in Psychology, 2023)
Different from studying the impact one enterprise performance from the single perspective of enterprise resilience or human resource management practices. Firstly, this thesis establishes a theoretical model between enterprise resilience, human resource management practice and enterprise performance. Moreover, analyzes the internal influencing factors of enterprise elasticity and human resource management practice respectively. Then, based on the fuzzy set qualitative comparative analysis method (FSQCA)to studies the influence of their internal influencing factors on enterprise performance, next evaluates the effect of the combination of the two internal factors on enterprise performance, and obtains the combination configuration of high/non-high performance, which is valuable for the improvement of enterprise resilience, the development of human resource management practice and the improvement of enterprise performance.